2023
DOI: 10.3390/jcm12155114
|View full text |Cite
|
Sign up to set email alerts
|

Trofinetide for Rett Syndrome: Highlights on the Development and Related Inventions of the First USFDA-Approved Treatment for Rare Pediatric Unmet Medical Need

Abstract: Rett syndrome (RTT) is a rare disability causing female-oriented pediatric neurodevelopmental unmet medical need. RTT was recognized in 1966. However, over the past 56 years, the United States Food and Drug Administration (USFDA) has authorized no effective treatment for RTT. Recently, Trofinetide was approved by the USFDA on 10 March 2023 as the first RTT treatment. This article underlines the pharmaceutical advancement, patent literature, and prospects of Trofinetide. The data for this study were gathered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Rett syndrome is a rare genetic neurodevelopmental disorder that is characterized by X-linked methyl-CpG-binding protein 2 (MECP2) mutation that can lead to permanent neurological damage or death in children (Hudu et al 2023;Parent et al 2023). Trofinetide is the first treatment approved for Rett syndrome in adults and pediatric patients (≥ 2 years) (Keam 2023e).…”
Section: Neurologymentioning
confidence: 99%
See 2 more Smart Citations
“…Rett syndrome is a rare genetic neurodevelopmental disorder that is characterized by X-linked methyl-CpG-binding protein 2 (MECP2) mutation that can lead to permanent neurological damage or death in children (Hudu et al 2023;Parent et al 2023). Trofinetide is the first treatment approved for Rett syndrome in adults and pediatric patients (≥ 2 years) (Keam 2023e).…”
Section: Neurologymentioning
confidence: 99%
“…Trofinetide was granted priority review, orphan, and fast track drug designations. Trofinetide is a synthetic peptidase-resistant analogue of the neuroprotective tripeptide glycine-proline-glutamate, a product of the cleavage of insulin-like growth factor 1 in the brain (Hudu et al 2023). The exact mechanism of action of trofinetide is not fully understood.…”
Section: Neurologymentioning
confidence: 99%
See 1 more Smart Citation
“…Trofinetide is a water-soluble analogue of glycine-proline-glutamate (GPE). GPE is an N-terminal tripeptide product of the cleavage of insulin-like growth factor 1 (IGF-1) found in the brain ( Hudu et al, 2023 ) and is neuroprotective at minimal doses. The mechanism of action of Trofinetide for treating Rett syndrome is not entirely understood, but it is thought to work on the same principle as GPE but with a longer half-life ( Bickerdike et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of Trofinetide for treating Rett syndrome is not entirely understood, but it is thought to work on the same principle as GPE but with a longer half-life (Bickerdike et al, 2009). Many studies have indicated that Trofinetide exerts its effect by enhancing synaptic activities, restoring synaptic structure, suppressing the effects of inflammatory compounds in the brain, increasing antioxidative reactions, decreasing injury-triggered cell death, and Frontiers in Pharmacology frontiersin.org 01 increasing the presence of IGF-1 in the central nervous system (Hudu et al, 2023). According to the results of the LAVENDER trial, this drug has demonstrated a promising improvement in the Rett syndrome behavioral questionnaire (RSBQ) total score compared to the placebo.…”
Section: Introductionmentioning
confidence: 99%